Laparoscopic peritoneal lavage or sigmoidectomy for perforated diverticulitis with purulent peritonitis: a multicentre, parallel-group, randomised, open-label trial. Issue 10000 (26th September 2015) - Vennix, Sandra; Musters, Gijsbert D; Mulder, Irene M; Swank, Hilko A; Consten, Esther C; Belgers, Eric H; van Geloven, Anna A; Gerhards, Michael F; Govaert, Marc J; van Grevenstein, Wilhelmina M; Hoofwijk, Anton G; Kruyt, Philip M; et al.
Summary: Background: Case series suggest that laparoscopic peritoneal lavage might be a promising alternative to sigmoidectomy in patients with perforated diverticulitis. We aimed to assess the superiority of laparoscopic lavage compared with sigmoidectomy in patients with purulent perforated diverticulitis, with respect to overall long-term morbidity and mortality. Methods: We did a multicentre, parallel-group, randomised, open-label trial in 34 teaching hospitals and eight academic hospitals in Belgium, Italy, and the Netherlands (the Ladies trial). The Ladies trial is split into two groups: the LOLA group comparing laparoscopic lavage with sigmoidectomy and the DIVA group comparing Hartmann's procedure with sigmoidectomy plus primary anastomosis. The DIVA section of this trial is still underway but here we report the results of the LOLA section. Patients with purulent perforated diverticulitis were enrolled for LOLA, excluding patients with faecal peritonitis, aged older than 85 years, with high-dose steroid use (≥20 mg daily), and haemodynamic instability. Patients were randomly assigned (2:1:1; stratified by age [<60 years vs ≥60 years]) using secure online computer randomisation to laparoscopic lavage, Hartmann's procedure, or primary anastomosis in a parallel design after diagnostic laparoscopy. Patients were analysed according to a modified intention-to-treat principle and were followed up after the index operation at least once in the outpatient setting and after sigmoidoscopy and stoma reversal, according to local protocols. The primary endpoint was a composite endpoint of major morbidity and mortality within 12 months. This trial is registered with ClinicalTrials.gov, number NCT01317485 . Findings: Between July 1, 2010, and Feb 22, 2013, 90 patients were randomly assigned in the LOLA section of the Ladies trial when the study was terminated by the data and safety monitoring board because of an increased event rate in the lavage group. Two patients were excluded for protocol violations. The primary endpoint occurred in 30 (67%) of 45 patients in the lavage group and 25 (60%) of 42 patients in the sigmoidectomy group (odds ratio 1·28, 95% CI 0·54–3·03, p=0·58). By 12 months, four patients had died after lavage and six patients had died after sigmoidectomy (p=0·43). Interpretation: Laparoscopic lavage is not superior to sigmoidectomy for the treatment of purulent perforated diverticulitis. Funding: Netherlands Organisation for Health Research and Development.